Attitude and Intention to Seek Mental Health Support Among Generation Z: Evaluating Instagram’s Role as a Mediator - Hadi, Ezra Aurelia Glenia; Destiwati, Rita (CHANNEL: Jurnal Komunikasi, 2025)
This study investigates the relationship between attitudes toward mental health and the intention to seek professional psychological support among Generation Z, with Instagram evaluated as a potential mediating variable. Drawing on the Theory of Planned Behavior (TPB), this research applies a quantitative, descriptive-correlational design involving 98 Indonesian respondents aged 15–24. The study employs Pearson correlation, validity and reliability tests, and mediation analysis using the Sobel test. Results reveal statistically significant positive relationships between attitude and intention (r = 0.442, p < 0.01), attitude and Instagram usage (r = 0.373, p < 0.01), and Instagram usage and intention (r = 0.436, p < 0.01). However, mediation analysis indicates that Instagram does not significantly mediate the relationship between attitude and intention (Z = 0.0734, p > 0.05). While Instagram is widely used by Generation Z for mental health-related content, this study finds that personal attitudes are more influential than platform engagement in shaping help-seeking intentions. The findings highlight the importance of enhancing mental health literacy and reducing stigma through both attitudinal and community-based interventions, with social media serving as a supportive—though not determining—channel. Future research should explore additional mediating factors such as social support, cultural norms, and mental health literacy across various digital platforms.